The Role of Teachers in Developing Students’ Reading Comprehension Through the Implementation of Webtoon Application - Mahdia Arafah; Rustam Pakpahan; Yani Lubis (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to describe the improvement in learning outcomes in spatial volume material using the TARL approach for class IV students at SDN 01 Kanigoro. This research was carried out using a type of Classroom Action Research (PTK) which was carried out in 2 cycles which aimed to determine the increase in the completeness of student learning outcomes through the TARL learning approach. The research subjects were 12 class IV students at SDN 01 Kanigoro. The research results show an increase in student learning outcomes in mathematics subjects using the TARL approach at SDN 01 Kanigoro. Based on the results of pre-cycle action activities, there were 3 students who completed and 9 students who did not complete. In the first cycle, there were 7 students who completed and 5 students who did not complete. while in the second cycle there were 11 students who completed it and 1 student who did not complete it. In conclusion, by using the TARL approach, student learning outcomes in class can improve.